Sakinah Family Education Model Based On Qur’ani And Local Wisdom - Samsul Hadi; Muhammad Syakur; Joni; Muh. Baehaqi; Sumarjoko; Husna Nashihin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
The family is the smallest social institution that plays a strategic role in shaping the character, morality, and identity of future generations. In Islamic perspective, the concept of sakinah family refers to a household built upon the values of tranquility, affection (mawaddah), and mercy (rahmah), as stated in the Qur’an, Surah Ar-Rum verse 21. However, in the midst of globalization, individualism, and instant culture, Qur’anic values are often marginalized, which makes it essential to strengthen family education based on Qur’anic principles integrated with local wisdom as a cultural identity. Qur’anic values such as monotheism (tauhid), piety (taqwa), ethics (adab), morality (akhlaq), consultation (shura), affection, and compassion provide strong spiritual and moral foundations for a sakinah family, while local wisdom contributes contextual educational mechanisms through traditions such as mutual cooperation (gotong royong), respect for parents and elders, the use of local language, traditional arts, and folklore that cultivate responsibility, solidarity, empathy, and pride in cultural identity. The integration of these two elements makes family education not only normative but also practical, relevant, and close to daily life. The study shows that developing a family education model based on Qur’anic values and local wisdom can produce generations who are faithful, morally upright, and culturally resilient in facing the challenges of globalization. Families that implement this model not only serve as the first and foremost place for character education but also function as agents in building a harmonious, peaceful, and prosperous society. Furthermore, the integration of religious and cultural values demonstrates that these two dimensions are not contradictory but complementary, capable of working hand in hand to strengthen moral integrity and social harmony. Thus, the development of a sakinah family education model rooted in both Qur’anic principles and local wisdom can be considered a strategic solution to address the moral and identity crisis, while simultaneously nurturing a society that is religious, culturally grounded, and characterized by noble values.